Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/acel.12403
|View full text |Cite
|
Sign up to set email alerts
|

CALHM1 and its polymorphism P86L differentially control Ca2+ homeostasis, mitogen‐activated protein kinase signaling, and cell vulnerability upon exposure to amyloid β

Abstract: SummaryThe mutated form of the Ca2+ channel CALHM1 (Ca2+ homeostasis modulator 1), P86L‐CALHM1, has been correlated with early onset of Alzheimer's disease (AD). P86L‐CALHM1 increases production of amyloid beta (Aβ) upon extracellular Ca2+ removal and its subsequent addback. The aim of this study was to investigate the effect of the overexpression of CALHM1 and P86L‐CALHM, upon Aβ treatment, on the following: (i) the intracellular Ca2+ signal pathway; (ii) cell survival proteins ERK1/2 and Ca2+/cAMP response e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…4A2 ). Growing evidence has showed that ERK signaling is crucial for progression of HCC 18 , 19 , and its activation can be triggered by changing cytosolic Ca 2+ level 9 , 20 . As Sorcin also regulates Ca 2+ homeostasis, so we focus on exploring whether Sorcin enhanced metastasis by activating ERK signaling in HCC.…”
Section: Resultsmentioning
confidence: 99%
“…4A2 ). Growing evidence has showed that ERK signaling is crucial for progression of HCC 18 , 19 , and its activation can be triggered by changing cytosolic Ca 2+ level 9 , 20 . As Sorcin also regulates Ca 2+ homeostasis, so we focus on exploring whether Sorcin enhanced metastasis by activating ERK signaling in HCC.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, depletion of the Ca 2+ homeostasis modulator 1 (CALHM1), a Ca 2+ channel involved in the regulation of cytosolic Ca 2+ levels, was found to downregulate ROS production, to increase the expression of HIF-1α and to display neuroprotective effects against ischemia in mice [ 164 ]. Notably, the mutation of this channel (P86L-CALHM1) got associated with Alzheimer's disease and mitochondrial Ca 2+ overload, potentially causing increased vulnerability of these cells to apoptotic stimuli [ [165] , [166] , [167] ].…”
Section: Crosstalk Between Ros and Ca 2+ In Age-rementioning
confidence: 99%
“…A meta-analysis suggested that the hCALHM1-P86L polymorphism is not an independent risk factor for LOAD but is associated with the age of onset [17]. Studies in mammalian cells showed that the P86L variant caused a partial inhibition of the effect of CALHM1 on Ca 2+ influx and amyloid-beta (Aβ) metabolism [9, 26, 34, 43]. However, no differences were observed in the gating and permeation properties between wild type (WT) and P86L-CALHM1 expressed in Xenopus oocytes or N2A cells, suggesting that the P86L polymorphism does not affect the intrinsic biophysical properties of hCALHM1 channels [20].…”
Section: Polymorphisms In Human Calhm1 Possibly Associate With Alzheimentioning
confidence: 99%
“…Exogenous expression of CALHM1 or P86L-CALHM1 elevated basal [Ca 2+ ] i [11, 26, 36]. In contrast, the magnitude of the Ca 2+ add-back response measured in cell populations was reduced in cells transiently expressing P86L-CALHM1 [8, 9, 26, 36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation